1993
DOI: 10.1530/acta.0.1290097
|View full text |Cite
|
Sign up to set email alerts
|

Twin genes and endocrine disease: CYP21 and CYP11B genes

Abstract: CYP21 and CYP11B genes have a common feature: they are "twin" genes. It seems as if doubling and subsequent drifting apart rendered these genes particularly sensitive to defect acquisition by mechanisms involving recombinatorial events. This creates specific difficulties in the molecular diagnosis of defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
6

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
(99 reference statements)
1
8
0
6
Order By: Relevance
“…This high level of sequence homology and co-localization together with potential recombination hot spots (Alu repeats, Chi sequence and human minisatellites repeats) may result in the functional gene becoming susceptible to recombination events such as gene conversion or crossing over among the functional gene and pseudogenes . Gene conversion events between homologous genes and their pseudogenes have been described in the pathogenesis of several genetic disorders, such as 21-hydroxylase deficiency (Helmberg 1993), von Willebrand disease (Eikenboom et al 1994) and Gaucher disease (Horowitz et al 1989). Among the 12 patients from the 11 unrelated families, homozygosity mapping showed that CGD in four patients is linked to NCF1, with all of these patients having the NCF1 DGT deletion.…”
Section: Discussionmentioning
confidence: 99%
“…This high level of sequence homology and co-localization together with potential recombination hot spots (Alu repeats, Chi sequence and human minisatellites repeats) may result in the functional gene becoming susceptible to recombination events such as gene conversion or crossing over among the functional gene and pseudogenes . Gene conversion events between homologous genes and their pseudogenes have been described in the pathogenesis of several genetic disorders, such as 21-hydroxylase deficiency (Helmberg 1993), von Willebrand disease (Eikenboom et al 1994) and Gaucher disease (Horowitz et al 1989). Among the 12 patients from the 11 unrelated families, homozygosity mapping showed that CGD in four patients is linked to NCF1, with all of these patients having the NCF1 DGT deletion.…”
Section: Discussionmentioning
confidence: 99%
“…The overall degree of divergence (exons plus introns) from the wild-type clones was found to be in the range 0.4% to 0.8%, thus rendering the p47-phox pseudogenes among the most conserved unprocessed pseudogenes known. Examples of other highly homologous unprocessed pseudogenes are the 21-hydroxylase pseudogene (CYP21A) (98% homology in exons and 96% homology in introns) (40), the von Willebrand factor pseudogene (96.9% overall homology) (41) and the ␤-glucocerebrosidase pseudogene (96% overall homology) (42).…”
Section: Discussionmentioning
confidence: 99%
“…As the products of crossing over and gene conversion events are virtually indistinguishable at the DNA level in higher eukaryotes, however, such events are commonly referred to as gene conversions (45). Gene conversion events between homologous genes and their pseudogenes have been described in the pathogenesis of several genetic disorders such as 21-hydroxylase deficiency (40), von Willebrand disease (46), and Gaucher disease (42), and have also been postulated for many clustered gene families (47). The presence of at least one p47-phox pseudogene carrying the GT deletion suggests that such events might also be responsible for the transfer of the GT deletion from the p47-phox pseudogene to the wild-type gene, thus leading to A47Њ CGD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, further investigation must be done for differential diagnosis of LOCAH due to 21-OH deficiency. Recently, the clinical presentations and molecular genetics of late onset 21-hydroxylase deficiency have been reviewed in considerable detail in the Ashkenazi Jewish, Hispanic, Italian, Yugoslav and American populations [1,3,[8][9][10][11]. The most common mutation is V281L (exon 7, codon 281), and it is present in 59.0% of the patients.…”
mentioning
confidence: 99%